DDAH1 Protects against Acetaminophen-Induced Liver Hepatoxicity in Mice - Xiyue Shen; Saddam Muhammad Ishaq; Qiao'e Wang; Juntao Yuan; Junling Gao; Zhongbing Lu (MDPI AG, 2022)
In many developed countries, acetaminophen (APAP) overdose-induced acute liver injury is a significant therapeutic problem. Dimethylarginine dimethylaminohydrolase 1 (DDAH1) is a critical enzyme for asymmetric dimethylarginine (ADMA) metabolism. Growing evidence suggests that liver dysfunction is associated with increased plasma ADMA levels and reduced hepatic DDAH1 activity/expression. The purpose of this study was to investigate the involvement of DDAH1 in APAP-mediated hepatotoxicity using Ddah1-/- and DDAH1 transgenic mice. After APAP challenge, Ddah1-/- mice developed more severe liver injury than wild type (WT) mice, which was associated with a greater induction of fibrosis, oxidative stress, inflammation, cell apoptosis and phosphorylation of JNK. In contrast, overexpression of DDAH1 attenuated APAP-induced liver injury. RNA-seq analysis showed that DDAH1 affects xenobiotic metabolism and glutathione metabolism pathways in APAP-treated livers. Furthermore, we found that DDAH1 knockdown aggravated APAP-induced cell death, oxidative stress, phosphorylation of JNK and p65, upregulation of CYP2E1 and downregulation of GSTA1 in HepG2 cells. Collectively, our data suggested that DDAH1 has a marked protective effect against APAP-induced liver oxidative stress, inflammation and injury. Strategies to increase hepatic DDAH1 expression/activity may be novel approaches for drug-induced acute liver injury therapy.